Any help or clues on this or any link for any tutorial please?Code:`A(n) = A(n-1) + B(n-1) + C(n-1)`

B(n) = 3^(n-1) - C(n-1)

C(n) = 3^(n-1) - B(n-1)

A(1) = B(1) = C(1) = 1

I tried using generating functions but failed...

Printable View

- 03-04-2009anirbanRecurrence Relation..Help needed!Code:
`A(n) = A(n-1) + B(n-1) + C(n-1)`

B(n) = 3^(n-1) - C(n-1)

C(n) = 3^(n-1) - B(n-1)

A(1) = B(1) = C(1) = 1

I tried using generating functions but failed... - 03-04-2009tabstop
Hint: Do you expect B and C to be different? Once you have B and C getting A should be easy.

- 03-04-2009anirban
Ya later i solved it using Generating functions :)

Anyway thanks for helping!